2019
DOI: 10.1111/apt.15179
|View full text |Cite
|
Sign up to set email alerts
|

Optimised infliximab monotherapy is as effective as optimised combination therapy, but is associated with higher drug consumption in inflammatory bowel disease

Abstract: Background: Combination treatment with azathioprine for 6-12 months is the preferred strategy for starting infliximab due to improved pharmacokinetics. However, optimised infliximab monotherapy with proactive dose escalations in case of low trough levels is a potentially safer but under-studied alternative.Aim: To compare the clinical success and infliximab consumption of combination vs optimised monotherapy strategies.Methods: We studied the clinical success and infliximab consumption with both strategies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…In a retrospective study of 149 patients with IBD (94 patients with Crohn's disease and 55 with ulcerative colitis), the less favourable pharmacokinetic profile initially observed with infliximab monotherapy could be overcome with dose escalation based on close therapeutic drug monitoring, with no difference in infliximab discontinuation, mucosal healing, hospitalisation, or long-term steroid use over a median follow-up of 19 months. 41 Concordant results were reported in a second retrospective study, in which early infliximab dose escalation resulted in similar clinical outcomes and infliximab trough concentrations regardless of concurrent immuno-modulator. 42 Taken together, although these data highlight the potential negative effect of immunomodulator withdrawal on anti-TNF pharmacokinetics and immunogenicity, an increased risk of relapse has not been shown, and proactive therapeutic drug monitoring emerges as a strategy to maintain anti-TNF efficacy.…”
Section: The Effect Of Immunomodulators Withdrawal On the Immunogenicsupporting
confidence: 61%
See 1 more Smart Citation
“…In a retrospective study of 149 patients with IBD (94 patients with Crohn's disease and 55 with ulcerative colitis), the less favourable pharmacokinetic profile initially observed with infliximab monotherapy could be overcome with dose escalation based on close therapeutic drug monitoring, with no difference in infliximab discontinuation, mucosal healing, hospitalisation, or long-term steroid use over a median follow-up of 19 months. 41 Concordant results were reported in a second retrospective study, in which early infliximab dose escalation resulted in similar clinical outcomes and infliximab trough concentrations regardless of concurrent immuno-modulator. 42 Taken together, although these data highlight the potential negative effect of immunomodulator withdrawal on anti-TNF pharmacokinetics and immunogenicity, an increased risk of relapse has not been shown, and proactive therapeutic drug monitoring emerges as a strategy to maintain anti-TNF efficacy.…”
Section: The Effect Of Immunomodulators Withdrawal On the Immunogenicsupporting
confidence: 61%
“…The authors also did a meta-analysis, which supported their findings. 46 The relapse rate at 1 year was 39% (95% CI [35][36][37][38][39][40][41][42][43][44] and 54% (49-59) at 2 years for patients with Crohn's disease, whereas the relapse rate for patients with ulcerative colitis or IBD unclassified was 35% (26-43) at 1 year and 42% (27-58) at 2 years. 46 A separate systematic review and meta-analysis produced similar results, with the overall risk of relapse after anti-TNF discontinuation being 44% in patients with Crohn's disease and 38% in those with ulcerative colitis.…”
Section: Withdrawal Of Anti-tnf Therapymentioning
confidence: 99%
“…Thirty-eight percent of patients needed IFX dose increase after withdrawal of the immunomodulator and 18% discontinued IFX [74]. The same authors showed that for similar effectiveness, combination therapy reduces IFX drug consumption and that IFX doses need to be increased upon discontinuation of the immunomodulator [75].…”
Section: Combination Therapymentioning
confidence: 99%
“…More recently, a post-hoc analysis of the SONIC trial suggested that the benefit of adding azathioprine to IFX could be explained solely by the resulting increment in IFX serum concentrations rather than the additive immunosuppressive effect of azathioprine 27 . In keeping with this, a subsequent prospective study observed that optimised IFX monotherapy is as effective as optimised combination therapy 28 . However, the IFX monotherapy group required significantly higher rates of treatment escalation, which makes this strategy unfavourable on a cost-effectiveness basis.…”
Section: Anti-tumour Necrosis Factor: Old Mechanism New Understandingsmentioning
confidence: 78%